2016
DOI: 10.1007/s10529-016-2048-9
|View full text |Cite
|
Sign up to set email alerts
|

Development of a sensitive molecular detection assay for mango malformation disease caused by Fusarium mangiferae

Abstract: Our assay provides a practical method for the early diagnosis so that proper prevention of the mango malformation disease can be developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…In the past decade, MMD has destroyed many thousands of hectares of mango in tropical and subtropical countries. Because of the economic importance of MMD, many studies have been performed on the occurrence (Steenkamp et al, 2000 ; Lima et al, 2009 ; Iqbal et al, 2011b ), pathogen genetic diversity (Iqbal et al, 2006 ; Liu et al, 2014 ), pathogen detection (Wu et al, 2016 ), pathogen cytology (Iqbal et al, 2010 ), infection life cycle (Freeman et al, 1999 ; Gamliel-Atinsky et al, 2009 ), and chemical control (Iqbal et al, 2011a ) of the disease, but research on the screening of mango germplasm for MMD resistance and on molecular mechanisms underlying MMD resistance and the pathogenicity of F. mangiferae is scarce (Singh, 2006 ). The main control measures against MMD include destruction of diseased mango branches, use of disease-free plant materials and fungicides.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, MMD has destroyed many thousands of hectares of mango in tropical and subtropical countries. Because of the economic importance of MMD, many studies have been performed on the occurrence (Steenkamp et al, 2000 ; Lima et al, 2009 ; Iqbal et al, 2011b ), pathogen genetic diversity (Iqbal et al, 2006 ; Liu et al, 2014 ), pathogen detection (Wu et al, 2016 ), pathogen cytology (Iqbal et al, 2010 ), infection life cycle (Freeman et al, 1999 ; Gamliel-Atinsky et al, 2009 ), and chemical control (Iqbal et al, 2011a ) of the disease, but research on the screening of mango germplasm for MMD resistance and on molecular mechanisms underlying MMD resistance and the pathogenicity of F. mangiferae is scarce (Singh, 2006 ). The main control measures against MMD include destruction of diseased mango branches, use of disease-free plant materials and fungicides.…”
Section: Introductionmentioning
confidence: 99%
“…Malformation of mango inflorescences (MMI) threatens mango productivity and causes significant damage to the mango industry 25,36 . Although Fusarium species have been implicated in malformation, the etiology of this disease remains obscure and effective control measures have not yet been identified 4,11,25 . Moreover, fungicides and other tested chemicals have not proved effective in controlling the disease 37,38 .…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we have reported higher content of ethylene in MMI 7,8 . In addition to producing ethylene 9 , Fusarium mangiferae leads to the overexpression of key mango genes 10,11 , which affects plant hormone homeostasis 12 and results in stress hormone ethylene formation 7 . Cyanide, a co-product of ethylene synthesis exerts adverse, toxic and long-term effects on plant growth and development 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…This technique was first demonstrated useful for measuring genetic diversity in plants and animals by Zietkiewicz et al (1994), and then shown to be useful for analysing the genetic diversity of plant-pathogenic fungi as well (Hannachi, Poli, Rezgui, Prassad, & Cherif, 2015;Menzies, Bakkeren, Matheson, Procunier, & Woods, 2003;Rampersad, 2013). Moreover, ISSR markers can be further converted into the more specific sequence-characterized amplified region (SCAR) markers (Aggarwal, Gupta, Banerjee, & Singh, 2011;Gao, Chen, & Liu, 2011;Wu et al, 2016). The species-specific SCAR markers have been successfully developed for identifying phytopathogenic fungi, such as Bipolaris sorokiniana (Aggarwal et al, 2011), Tilletia controversa (Gao et al, 2011) and Fusarium mangiferae (Wu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ISSR markers can be further converted into the more specific sequence-characterized amplified region (SCAR) markers (Aggarwal, Gupta, Banerjee, & Singh, 2011;Gao, Chen, & Liu, 2011;Wu et al, 2016). The species-specific SCAR markers have been successfully developed for identifying phytopathogenic fungi, such as Bipolaris sorokiniana (Aggarwal et al, 2011), Tilletia controversa (Gao et al, 2011) and Fusarium mangiferae (Wu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%